Impact of oral health guidance on the tongue‐lip motor function of outpatients at a dental hospital. (24th October 2021) - Hatanaka, Yukiko; Furuya, Junichi; Sato, Yuji; Uchida, Yoshiki; Osawa, Tokiko; Shichita, Toshiharu; Suzuki, Hiroyuki; Minakuchi, Shunsuke
Abstract: Objective: To clarify the effect of oral health guidance on tongue‐lip motor function in the outpatients visiting the Showa University Dental Hospital (Tokyo, Japan). Background: The management of the oral function of older people visiting a dental hospital is important. Previous studies have revealed that tongue‐lip motor function is easy to improve. However, the impact of oral health guidance on tongue‐lip motor function in the outpatients of dental hospital requires further elucidation. Materials and Methods: The participants (n = 35) included patients who were diagnosed with low tongue‐lip motor function on evaluation by oral diadochokinesis (ODK) at the outpatient clinic. They underwent a second examination approximately 6‐12 months later. Their demographic characteristics were recorded. Oral health guidance was provided through an educational leaflet on oral hypofunction when the participants visited the clinic. It included content on tongue twisters, voice training and a range of movement and muscle training of the tongue and lip. Results: Following oral health guidance on tongue‐lip motor function, the ODK values changed from 5.6 at the first examination to 6.0 at the second for /pa/, from 5.6 to 5.8 for /ta/ and from 5.2 to 5.4 for /ka/. This improvement was not significantly associated with age, sex, measurement period or number of visits. Conclusion: The findings of this longitudinal study suggested that oral health guidance using an oral hypofunction educational leaflet may be effective in improving the tongue‐lip motor function of outpatients who had low tongue‐lip motor function, regardless of the measurement period or the number of visits to the dental hospital.